1983
DOI: 10.1007/bf01311733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an antiulcer drug, sucralfate (A basic aluminum salt of sulfated disaccharide), on experimental gastric lesions and gastric secretion in rats

Abstract: The effects of oral sucralfate, a basic aluminum salt of sulfated disaccharide, on various experimental gastric lesions and on gastric secretion were studied in rats. Sucralfate at 300 mg/kg potently inhibited the development of Shay ulcers and indomethacin- and aspirin-induced erosions. The drug at 1000 mg/kg also potently inhibited histamine-induced erosions. Water-immersion stress-induced erosions were inhibited with 1000 mg/kg of the drug, but the degree of inhibition was weaker than that seen in other typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
1

Year Published

1984
1984
1995
1995

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 16 publications
3
20
1
Order By: Relevance
“…Sucralfate caused no inhibition of gastric pepsin activity and had no preventive effect against aspirin-induced erosions, while TA-2711 did. The result of sucralfate in gastric pepsin activity was consistent with that re ported by Okabe et al (18). On the other hand, Okabe et al (18) …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Sucralfate caused no inhibition of gastric pepsin activity and had no preventive effect against aspirin-induced erosions, while TA-2711 did. The result of sucralfate in gastric pepsin activity was consistent with that re ported by Okabe et al (18). On the other hand, Okabe et al (18) …”
Section: Discussionsupporting
confidence: 88%
“…The result of sucralfate in gastric pepsin activity was consistent with that re ported by Okabe et al (18). On the other hand, Okabe et al (18) …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The pathogenesis of histamine-induced lesions remains un known. In the model of histamine-induced lesions produced by histamine at 100 mg/kg, i.p., propantheline bromide and cimetidine were effective for inhibiting the lesions, thereby indicating the participation of gastric acid and pepsin (13). In another study, it was confirmed that histamine interfered with gastric mucosal circulation in guinea pigs (14).…”
mentioning
confidence: 83%
“…The stomach was put into 10% formalin for microscopy. The following agents were given to various groups of 10 were given by oral gastric intubation in a volume of 0.5 ml/100 g of body weight twice (9:00 AM, 6:00 PM) or thrice (9:00 AM, 2:00, 7:00 PM) daily for 4 days during the prednisolone treatment. PG12, firstly dissolved in 1 M Tris buffer and stored in a deep freezer, was diluted with 1.25% NaHCO3 to a desired concentration and given subcutaneously in a volume of 0.2 ml/ 100 g of body weight, 4 times (9:00 AM, 0:00, 3:00, 6:00 PM) daily.…”
mentioning
confidence: 99%